Learning Accommodation for Slow Learners in Inclusive Elementary Schools - Sukinah; Mumpuniarti; Murdiyani, Kenanga Kusuma (INKLUSI, 2024)
Abstract Teachers should understand slow learners to reduce behavioral problems. Thus, this study aims to identify forms of practical action taken by teachers to help with learning problems faced by slow learners. The method used is research and development to develop a questionnaire about teacher actions in overcoming learning problems faced by slow learners. The subjects of this study were 40 regular elementary school teachers in the Special Region of Yogyakarta. Furthermore, the data analysis technique used is quantitative with percentages. The results of the study show that regular elementary school teachers have taken tactical action to provide solutions to the learning problems of slow learners. Most teachers help students by maximizing student potential, meaning that they support all efforts students can make to learn. However, teachers have not utilized learning resources and media to bridge the metacognitive learning of slow learners. . Consequently, teachers need training on effective learning media for the development of students' metacognition.